HUBUNGAN POWER OTOT TUNGKAI DENGAN KEMAMPUAN LOMPAT JAUH PADA SISWA KELAS XI SMAN 1 KULISUSU - Siti Erwinda Pratiwi; Muhammad Rusli; Abdul Saman (Journal Olympic (Physical Education, Health and Sport), 2021)
The aims of this study was to determine the relationship between leg muscle power and long jump ability of students in class XI SMAN 1 Kulisusu. The population in this study was the total number of students in class XI SMAN 1 Kulisusu, with 320 people consisting of 140 boys and 180 girls using the proposive random sampling technique. The instrument used to measure leg muscle power is by using the standing broad jump test, while the instrument used to measure the long jump ability is the long jump. The data analysis technique used analysis prerequisite test, namely normality, linearity and hypothesis testing using the product moment correlation test. The research data were analyzed using statistical technique of 0,05product moment. In the study, it was concluded that there was a relationship between leg muscle power and long jump ability in students of class XI SMAN 1 Kulisusu where rxy = 0.39 at a significant level of 0.029 <0.05. While the coefficient of termination (r2) = 0.15 or 15%. This shows that the level of correlation between the leg muscle power variable (X) and the long jump ability (Y) is at a low correlation. Besides, 85% is influenced by elements of other physical conditions. The results of this study indicate that there is a significant relationship between leg muscle power and long jump ability in class XI students of SMAN 1 Kulisusu